Oligoethylene glycol side chains increase charge generation in organic semiconductor nanoparticles for enhanced photocatalytic hydrogen evolution - Kosco,J; Gonzalez-Carrero,S; Howells,CT; Zhang,W; Moser,M; Sheelamanthula,R; Zhao,L; Willner,B; Hidalgo,TC; Faber,H; Purushothaman,B; Sachs,M; et al. (Advanced Materials, 2021)
Organic semiconductor nanoparticles (NPs) composed of an electron donor/acceptor (D/A) semiconductor blend have recently emerged as an efficient class of hydrogen-evolution photocatalysts. It is demonstrated that using conjugated polymers functionalized with (oligo)ethylene glycol side chains in NP photocatalysts can greatly enhance their H2-evolution efficiency compared to their nonglycolated analogues. The strategy is broadly applicable to a range of structurally diverse conjugated polymers. Transient spectroscopic studies show that glycolation facilitates charge generation even in the absence of a D/A heterojunction, and further suppresses both geminate and nongeminate charge recombination in D/A NPs. This results in a high yield of photogenerated charges with lifetimes long enough to efficiently drive ascorbic acid oxidation, which is correlated with greatly enhanced H2-evolution rates in the glycolated NPs. Glycolation increases the relative permittivity of the semiconductors and facilitates water uptake. Together, these effects may increase the high-frequency relative permittivity inside the NPs sufficiently, to cause the observed suppression of exciton and charge recombination responsible for the high photocatalytic activities of the glycolated NPs.